Comparison of Endometrial Microbiota Results Between Patients with Unexplained Infertility and Fertile Patients through 16s rRNA Sequencing - Gonca Ozten Dere; Cagman Tan; Sezcan Mumusoglu; Pinar Zarakolu; Gurkan Bozdag (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The primary objective of our study was to compare the endometrial microbiota profiles of women with unexplained infertility and fertile women.